Dr. Edwin Wright Letters: George Cooke (Alice B. Donahue Library & Archives, 1960)
Mr. George Cooke writes of life in Athabasca Landing before the automobile arrived. Businesses, freighting, the fur trade and numerous settlers are mentioned by name. 2 pages